The Translation of Samuel Beckett’s ’mirlitonnades’ by Three Spanish Authors - Garre García, Mar (Complutense Journal of English Studies, 2020)
The mirlitonnades are short poems written by Samuel Beckett between 1976 and 1978. These minimalistic pieces reflect the poetic idiosyncrasies in his literary career and also in his personal life. Although Spanish literary culture has not been significantly affected by the work of Samuel Beckett —with some notable exceptions— it is surprising that the mirlitonnades have been translated five times into Spanish. In this study, I will focus on three of those versions —Loreto Casado (1998), Jenaro Talens (2000) and José Luis Reina Palazón (2014)— with the objective of identifying common sources of interest for these translators in Beckett’s poems. Attention will also be paid to the main points of convergence among the different versions, as well as their dissimilarities. In addition, the predominant methods that they adopted in translating the mirlitonnades will be examined. The study of their lexical choices will ultimately reveal different approaches to Beckett’s work, as well as the various images of Beckett as a poet that Spanish readers might have acquired through each of these versions.